2011
DOI: 10.1159/000323445
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological and Psychopathological Variables Related to Emotional Instability: A Study of Their Capability to Discriminate Patients with Bulimia Nervosa from Healthy Controls

Abstract: Objective: To analyze the capability of a set of neurobiological and psychopathological variables to discriminate bulimia nervosa (BN) patients from healthy controls. Method: Seventy-five female patients with purging BN and 30 healthy controls were compared for psychopathology (impulsivity, borderline personality traits, depressive symptoms and self-defeating personality traits) and neurobiological parameters reflecting hypothalamic-pituitary-adrenal axis activity (morning serum cortisol before and after dexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 144 publications
3
16
0
1
Order By: Relevance
“…Our ED patients had a lower capability to suppress cortisol after DXT administration than the HC. This finding has been already reported in literature, including previous papers from our group . According to the existing data, it seems that approximately half of AN patients and one third of patients with BN are non‐suppressors .…”
Section: Discusionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our ED patients had a lower capability to suppress cortisol after DXT administration than the HC. This finding has been already reported in literature, including previous papers from our group . According to the existing data, it seems that approximately half of AN patients and one third of patients with BN are non‐suppressors .…”
Section: Discusionsupporting
confidence: 89%
“…We consider that the finding in our patients of plasma and saliva basal cortisol levels lower to those of the HC group can be justified by the fact that the basal assessment was made in a laboratory setting; so, and even including a rest period before the collection of blood samples, the probands could be in a high degree of activation due to the anxiety caused by the tests to be done. In addition, and according to the results from some studies, hypercortisolism can be associated with specific clinical manifestations and can be mediated by other factors which have not been assessed in our study, as for example alcohol use …”
Section: Discusionsupporting
confidence: 68%
See 1 more Smart Citation
“…Contrary to primary psychopathic subjects, traits such as hostility, aggression, suicidal behavior, and impulsivity in both healthy controls and groups of neurotic, violent, and/or suicidal personality disordered patients have been mainly related to lower HVA levels (r ≈ -0.32) (Coccaro and Lee, 2010;Engström et al, 1999;Limson et al, 1991;Sher et al, 2006;Vaz-Leal et al, 2011), or to higher HVA levels in the context of serotonergic deficiency (Nilsson et al, 2010). Therefore, higher DA functioning could specifically relate to antisocial traits in primary psychopathic individuals, whereas in non-psychopathic (or secondary psychopathic) individuals characterized by emotional dysregulation and serotonergic deficiency, it may be a deregulation of DA activity (both lower and higher HVA levels) which is associated with aggression and impulsivity.…”
Section: Tonic/population Mesolimbic Da Activity In Psychopathymentioning
confidence: 98%
“…Our ED patients also responded in a similar way, but with specific patterns of response: While in AN patients the decrease in the number of lymphocytes was similar to that in the HC, the process was three to four times more intense in the BN patients. We consider this discordance perhaps to be due to the existence of differences in the reactivity to stress of the HPA and SAM axes in AN and BN (Garaci et al, 2019; A. M. Monteleone et al, 2015, 2017; P. Monteleone et al, 2011, 2012, 2014; Nagata, Yamada, Iketani, & Kiriike, 2006; Paszynska et al, 2016; Pirke et al, 1992; Vaz‐Leal, Rodríguez‐Santos, García‐Herráiz, & Ramos‐Fuentes, 2011; Vaz‐Leal et al, 2007, 2010; Vaz‐Leal, Rodríguez‐Santos, García‐Herráiz, Monge‐Bautista, & López‐Vinuesa, 2011). In a recent study, we reported that AN‐restricting type patients display a pattern of stress‐induced cortisol release similar to that of healthy individuals, whereas a blunted cortisol response is observed in BN patients (Vaz‐Leal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%